Mitigating IT Risk of Bank Syariah Indonesia: A Study of Cyber Attack on May 8, 2023 - Rini Fitriani; Rokhmat Subagiyo; Binti Nur Asiyah (UIN Siber Syekh Nurjati Cirebon, 2023)
The rapid development of information technology in Indonesia cannot be overlooked. Technological advancements in all fields must be implemented, including in the world of Islamic banking. Customers need convenience, smoothness, security, and flexibility in digital banking services. Bank Syariah Indonesia (BSI) is the largest Islamic bank in Indonesia. The hashtag